2021
DOI: 10.3390/ani11061714
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Plasma Analytes Reflecting Metabolic Adaptation to the Different Stages of the Lactation Cycle in Healthy Multiparous Holstein Dairy Cows Raised in High-Welfare Conditions

Abstract: Here, we tested the changes occurring in several plasma analytes during different stages of the lactation cycle of high welfare raised multiparous Holstein cows, and provided reference intervals (RI) for plasma analytes concentrations. Eleven high-welfare farms (HWF) located in Northern Italy were selected and their herds used to recruit 361 clinically healthy cows undergoing the dry (from −30 to −10 days from real calving; DFC), the postpartum (from 3 to 7 DFC), the early lactation (from 28 to 45 DFC) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
3
14
0
Order By: Relevance
“…Earlier reports suggested that nutrient partitioning and other metabolic activities are the essential physiological processes that subsequently help in subclinical ketosis (SCK) prevention (3) and improving cow's health during the transition and early lactation periods of dairy cattle. In general, the fatty acids, blood metabolites and GH directly or indirectly influence animals in terms of growth, reproduction, welfare condition, during the transition and early lactation periods (4)(5)(6)(7). During the early lactation period, dairy cows experience tremendous physiological and metabolic changes (8)(9)(10), accompanied by fetal development, milk production, high energy intake and a negative energy balance (NEB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports suggested that nutrient partitioning and other metabolic activities are the essential physiological processes that subsequently help in subclinical ketosis (SCK) prevention (3) and improving cow's health during the transition and early lactation periods of dairy cattle. In general, the fatty acids, blood metabolites and GH directly or indirectly influence animals in terms of growth, reproduction, welfare condition, during the transition and early lactation periods (4)(5)(6)(7). During the early lactation period, dairy cows experience tremendous physiological and metabolic changes (8)(9)(10), accompanied by fetal development, milk production, high energy intake and a negative energy balance (NEB).…”
Section: Introductionmentioning
confidence: 99%
“…However, insufficient food intake and the physiological changes after calving lower the appetite, which does not recover quickly (appetite peak can be attained 10-12 weeks after birth). The energy obtained from the animal's body through dry matter (DM) absorption cannot meet the body's requirements, which are significant during lactation (7,18). Therefore, the animal's body first mobilizes hepatic glycogen and then fats and proteins to accelerate gluconeogenesis to maintain the energy balance needed for lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alongside the latter, another possible explanation could be represented by a transient impairment of kidney function in this phase. The latter could be supported by the higher plasma concentration of creatinine after dry-off 5 , 44 , since circulating creatinine is related to the kidneys’ ability to remove it from the bloodstream 45 . Moreover, advanced glycation end products are recognized as pro-inflammatory mediators, their formation is related to that of reactive oxygen metabolites, and can be formed as a result of oxidative stress and along inflammatory pathways 46 .…”
Section: Resultsmentioning
confidence: 99%
“…As previously discussed, the amount of OCFA in milk is mainly related to ruminal microorganism synthesis and partly to endogenous production in the mammary gland. On the other hand, GGT is one of the most reliable markers of liver damage and oxidative stress and is susceptible to variation with increased liver activity during early lactation [64,65]. Vlaeminck et al [66] observed that the milk OCFA profile differed from the intestinal OCFA profile and was more closely related to the profile in plasma TAG.…”
Section: Ggtmentioning
confidence: 99%